Peran customer reviews dan imitation of influencers terhadap purchase intention yang dimoderasi trust pada luxury restaurant di Jakarta - Cintalia, Meivina; Yenita, Yenita (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
This study aims to analyze the effect of customer reviews and imitation of influencers on purchase intention at a luxury restaurant in Jakarta with the moderating role of trust. The research study contains a descriptive approach to research with quantitative analysis with 150 respondents. The data analysis technique used in this study is Partial Least Squares-Structural Equation Modeling (PLS-SEM). The result of this research indicates that the variable of customer reviews and imitation of influencers have a positive and significant impact on purchase intention. However, trust as a moderating variable was also not validated in this study. The result of this study hopefully could give a contribution to entrepreneurs, especially those in the luxury restaurant business, to gain a deeper understanding of effective business strategies. Penelitian ini bertujuan untuk menguji pengaruh customer reviews dan imitation of influencers terhadap purchase intention pada luxury restaurant yang ada di Jakarta. Penelitian ini mengandung pendekatan penelitian deskriptif dengan analisa kuantitatif terhadap responden sebanyak 150 orang. Teknik analisis data yang digunakan dalam penelitian ini adalah metode analisis Partial Least Squares-Structural Equation Model (PLS-SEM). Hasil dari penelitian ini menunjukkan bahwa variabel customer reviews dan imitation of influencers berpengaruh positif dan signifikan terhadap purchase intention. Namun, trust sebagai variabel moderasi tidak dapat divalidasi dalam penelitian ini. Hasil pada penelitian ini diharapkan dapat memberikan kontribusi bagi pengusaha terutama dalam usaha luxury restaurant untuk dapat memperoleh pemahaman lebih mengenai strategi usaha yang efektif.